2016
DOI: 10.1089/jmf.2015.0077
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Preventive Administration ofChlorellasp. on Visceral Pain and Cystitis Induced by a Single Administration of Cyclophosphamide in Female Wistar Rat

Abstract: Chlorella sp. is a green microalgae containing nutrients, vitamins, minerals, and chlorophyll. In some communities, Chlorella sp. is a traditional medicinal plant used for the management of inflammation-related diseases. In a rat model, ROQUETTE Chlorella sp. (RCs) benefits were investigated on visceral pain and associated inflammatory parameters related to cystitis both induced by cyclophosphamide (CYP). RCs was orally administered every day from day 1-16 (250 and 500 mg/kg body weight). Six hours after an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The control rats received volume-matched saline i.p. The doses of the administered agents were chosen based on the literature data and were confirmed/adjusted in our laboratory in preliminary experiments (Hidalgo-Lucas et al 2016 ; Juszczak et al 2010 ; Kobayashi et al 2009 ; Wróbel and Rechberger 2015 ; Wróbel and Rechberger 2016a ; Wróbel and Rechberger 2016b ; Wróbel and Rechberger 2016c ).…”
Section: Methodsmentioning
confidence: 99%
“…The control rats received volume-matched saline i.p. The doses of the administered agents were chosen based on the literature data and were confirmed/adjusted in our laboratory in preliminary experiments (Hidalgo-Lucas et al 2016 ; Juszczak et al 2010 ; Kobayashi et al 2009 ; Wróbel and Rechberger 2015 ; Wróbel and Rechberger 2016a ; Wróbel and Rechberger 2016b ; Wróbel and Rechberger 2016c ).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, various in vivo studies on CV have revealed that they exhibit antioxidative [ 40 ], hepatoprotective [ 41 ], antibacterial [ 16 ], and antitumor activity [ 42 ]. An increasing number of studies have demonstrated that CV and its extracts enhance the immune function in vitro and in vivo [ 43 , 44 , 45 ]. Furthermore, some researchers have focused on the immunomodulation of the protein hydrolysate from CV, and found that CV protein hydrolysate stimulated both humoral and cell mediated immune functions positively, such as T-dependent antibody response and the reconstitution of delayed-type hypersensitivity response [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The extracts were previously registered in Serbia as a di-karotene i vitamin A. Pored toga, hlorela se koristi kao proteinsko sredstvo za ljudsku upotrebu i kao alternativni antibiotik u stočarskoj proizvodnji. Potvrđeno je da hlorela takođe ima imunomodulatornu aktivnost kod pilića, poboljšavajući performanse rasta i kvalitet kokošijih jaja [35].…”
Section: Methodsunclassified
“…In addition, chlorella is used as a protein supplement for human consumption and as an alternative antibiotic in livestock production. Chlorella has also been confirmed to have immunomodulatory activity in chickens, improving growth performance and egg quality [35].…”
Section: Spirulina and Chlorellamentioning
confidence: 99%